Niclosamide ethanolamine improves kidney injury in db/db mice. (October 2018) - Han, Pengxun; Zhan, Hongyue; Shao, Mumin; Wang, Wenjing; Song, Gaofeng; Yu, Xuewen; Zhang, Chunlei; Ge, Na; Yi, Tiegang; Li, Shunmin; Sun, Huili
Abstract: Aims: Early diabetic kidney disease (DKD) is characterized by renal hypertrophy and albuminuria. The mTOR signal pathway is closely related to DKD. This study was performed to determine the renal protection of niclosamide ethanolamine salt (NEN) which was identified as mTOR inhibitor. Methods: Type 2 diabetes (T2D) db/db mice were used and divided into db/db and db/db + NEN groups. Lean wild type mice served as T2D-control. NEN treatment lasted for 12 weeks. The kidney morphological changes, urine indices, blood glucose and metabolic symptoms were evaluated. In addition, the effects of NEN on kidney mitochondria and mTOR/4E-BP pathway were also measured. Results: NEN could prevent diabetic kidney hypertrophy and alleviate glomerular mesangial expansion, attenuate GBM and TBM thickening in db/db mice. It also restored podocyte dysfunction, reduced urinary albumin, NAG, NGAL, and TGF-β1 excretion. Specifically, it could uncouple kidney mitochondria and significantly inhibit renal cortical activation of mTOR/4E-BP1 pathway. Conclusions: This study demonstrated that NEN could improve kidney injury in db/db mice and has the potential to translate to future clinical studies.